(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
The present study was designed to investigate the antioxidant effect of Garcinia indica Linn fruit extract on heart weight, lipid peroxidation; enzymatic and non-enzymatic antioxidants against isoprenaline hydrochloride (ISO) induced myocardial infarction (MI) in rats. Group II rats treated with Isoprinosine (25 mg/kg. b.w. i.p.) recorded significant (p<0.05) increase in heart weight and cardiac lipid peroxidation whereas there was significant decrease in enzymatic and non-enzymatic antioxidants. Pretreatment with Garcinia indica fruit extract (250 mg/kg b.w and 500 mg/kg b.w. per day/p.o.) for 30 consecutive days followed by ISO injections on 29th and 30th days in group III and IV rats showed that significant decrease in heart weight and cardiac lipid peroxidation where as the enzymatic antioxidant and nonenzymatic activities, were significantly increased when compared to ISO treated group II. Hence, the present study suggested that the fruit extract of Garcinia indica was effective as cardioprotective and antioxidant agent.